2019
DOI: 10.2147/copd.s220850
|View full text |Cite
|
Sign up to set email alerts
|

<p>Efficacy and Safety of Budesonide/Glycopyrrolate/Formoterol Fumarate Metered Dose Inhaler Formulated Using Co-Suspension Delivery Technology in Japanese Patients with COPD: A Subgroup Analysis of the KRONOS Study</p>

Abstract: Background: KRONOS, a Phase III, multicenter, randomized, double-blind study (NCT02497001) conducted in Canada, China, Japan, and the USA, assessed the efficacy and safety of budesonide/glycopyrrolate/formoterol fumarate metered dose inhaler (BGF MDI), a triple fixed-dose combination therapy, relative to dual therapies in patients with moderate-to-very severe COPD. Here we present findings from the Japanese subgroup of KRONOS. Methods: Patients received BGF MDI 320/18/9.6μg, glycopyrrolate/formoterol fumarate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…All treatments were well tolerated, and there was no evidence that the profile or frequency of individual TEAEs differed based on the duration of exposure within or across treatment groups. Safety and efficacy results over 52 weeks were generally in agreement with findings from the global population and the Japanese subgroup of KRONOS over 24 weeks, 3,10 and support the long-term tolerability of BGF MDI in Japanese patients with moderateto-very severe COPD.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…All treatments were well tolerated, and there was no evidence that the profile or frequency of individual TEAEs differed based on the duration of exposure within or across treatment groups. Safety and efficacy results over 52 weeks were generally in agreement with findings from the global population and the Japanese subgroup of KRONOS over 24 weeks, 3,10 and support the long-term tolerability of BGF MDI in Japanese patients with moderateto-very severe COPD.…”
Section: Discussionsupporting
confidence: 81%
“…Full demographic characteristics of the Japanese safety population have been published. 10 In brief, the majority of Japanese patients were male (94.2%) with a mean age of 69.5 years. Eighty percent of patients had not experienced a COPD exacerbation in the previous year, and only 31.5% were receiving an ICS at study entry.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed the use of these inhalers among individuals prior to enrolment in pharmaceutical interventional studies that were conducted worldwide, including the United States, Europe, and Asia. Figure 4 compares the uses of ICS-containing (A) and LAMAcontaining (B) regimens in a subgroup analysis of Japanese COPD patients to those in the complete datasets of COPD patients worldwide (41)(42)(43)(44)(45)(46)(47)(48). ICS use was less frequent, and LAMA use was more frequent in Japan.…”
Section: Adherence To Inhaled Medicationsmentioning
confidence: 99%
“…Another report showed that the percentage of COPD patients using home-based LTOT to all patients using home based LTOT has been approximately 50% over time (53). In a single center prospective study, of 101 COPD patients who showed mild hypoxaemia (PaO 2 <80 Torr) at the baseline evaluation, 10 (10%) developed KRONOS (45,46), and SHINE (47,48) studies were conducted all over the world, including in the United States, Europe, Asia, and Japan.…”
Section: Long-term Oxygen Therapy (Ltot)mentioning
confidence: 99%